1994
DOI: 10.1002/prot.340190203
|View full text |Cite
|
Sign up to set email alerts
|

1.56 Å structure of mature truncated human fibroblast collagenase

Abstract: The X-ray crystal structure of a 19 kDa active fragment of human fibroblast collagenase has been determined by the multiple isomorphous replacement method and refined at 1.56 A resolution to an R-factor of 17.4%. The current structure includes a bound hydroxamate inhibitor, 88 waters and three metal atoms (two zincs and a calcium). The overall topology of the enzyme, comprised of a five stranded beta-sheet and three alpha-helices, is similar to the thermolysin-like metalloproteinases. There are some important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(194 citation statements)
references
References 23 publications
10
179
0
5
Order By: Relevance
“…Three of the Asn double-clash examples are consistent with the possibility of chemical de-amidation of the side-chain: 1CSE Asn158E (subtilisin; Bode et al, 1987), 1HFC Asn206 (collagenase; Spurlino et al, 1994), and 1LUC Asn12 (luciferase; Fisher et al, 1996), which is shown in Figure 8. The tight interactions around Asn12, including two H-bonds to backbone NH groups, de®nitely require an O d for the left-hand branch of the amide.…”
Section: Summary Of Final Assignmentssupporting
confidence: 58%
“…Three of the Asn double-clash examples are consistent with the possibility of chemical de-amidation of the side-chain: 1CSE Asn158E (subtilisin; Bode et al, 1987), 1HFC Asn206 (collagenase; Spurlino et al, 1994), and 1LUC Asn12 (luciferase; Fisher et al, 1996), which is shown in Figure 8. The tight interactions around Asn12, including two H-bonds to backbone NH groups, de®nitely require an O d for the left-hand branch of the amide.…”
Section: Summary Of Final Assignmentssupporting
confidence: 58%
“…These peptides were chosen based on knowledge gained from structure-function studies performed on other MMPs. The structures for the catalytic domains of several members of the MMP family have recently become available including human fibroblast collagenase (MMP-1) (22-24), human stromelysin-1 (MMP-3) (25,26), human matrilysin (MMP-7) (27), and human neutrophil collagenase (MMP-8) (28 -30). These structures revealed that the SЈ 1 subsite is the most well defined pocket in these MMPs and consists of a hydrophobic pocket which varies greatly in its depth.…”
Section: Figmentioning
confidence: 99%
“…How collagenases interact with collagen and how the Hpx domain endows these enzymes with collagenolytic activity is not clearly understood. Another enigma of collagenolysis became apparent when the crystal structures of MMP-1Cat (8)(9)(10), MMP-8Cat (11,12), and full-length pig MMP-1 (6) were solved: The catalytic cleft of these enzymes is too narrow to accommodate collagen in its native triple-helical conformation. A number of hypotheses have been proposed to explain how collagenases may destabilize and cleave triple-helical collagen (13)(14)(15)(16), and we have experimentally demonstrated that MMP-1 unwinds triple-helical collagen locally before peptide bond hydrolysis (17,18).…”
mentioning
confidence: 99%